A note on strong convergence of implicit scheme for SDEs under local one-sided Lipschitz conditions. Issue 2 (1st February 2021) - Tan, Li; Yuan, Chenggui
Abstract : In this paper, we aim to study strong convergence of theta-EM scheme for stochastic differential equations under a local one-sided Lipschitz condition. Since the existence and uniqueness of theta-EM solution cannot be guaranteed under the local one-sided Lipschitz condition, a modified theta-EM scheme is proposed, and strong convergence of the numerical solution to the exact solution is given.